Development of computational algorithms and thermodynamic models for multiphase, multicomponent CO2 mixtures - Νικολαΐδης, Ηλίας (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Χημικών Μηχανικών, 2015)
Carbon Capture and Sequestration (CCS) is a technology designed to reduce carbon dioxide (CO2) emissions from large point sources of production. CCS has grown in recent years from lab and pilot scale activity to a full blown industrial process. Preliminary conceptual design, detailed design, simulation and optimization of a CCS process require, among others, accurate knowledge of the physical properties of the chemical system involved. CO2 is typically captured from fossil fuel power plants and is transported through pipelines to the appropriate storage location. This fluid stream contains different chemical impurities in various concentrations, that depend on the initial process and the type of pre-treatment imposed to the stream prior to transportation. Accurate knowledge of the physical properties of the chemical system as a function of temperature, pressure and composition is required. Quite often, the system exists in more than one phase (i.e., liquid, vapor and/or solid) and as a result process design calculations have to take into account the phase equilibrium conditions and also the composition of the relevant phases and the respective physical property values. The calculation of the physical properties of the stream and the phase equilibria are calculated traditionally with Equations of State (EoS). The two challenges that arise are the accurate prediction or correlation of the physical properties of the system and the conditions of instability, where the system is going to split into two or more coexisting phases. Moreover, calculation of phase equilibria itself generates various computational challenges and the need of robust algorithms has driven a wealth of mathematical formulations of the phase equilibrium problem. In this work, a robust numerical scheme for the calculation of constant composition (isoplethic) phase diagrams of complex multicomponent mixtures has been developed. The scheme refers to the sequential calculation of the phase envelope of a mixture by guiding the estimation for the equilibrium curve via the introduction of a ―spring‖ that sets the slope value of the modified tangent plane distance with respect to either temperature or pressure. A simple variation of the proposed method allows direct estimation of the Cricondentherm (maximum temperature) and/or Cricondenbar (maximum pressure) points, thus avoiding the calculation of the entire phase diagram. Extensive tests of the proposed scheme for different types of phase diagrams, using both cubic and higher order EoS have been performed. Moreover, several EoS have been used to model the vapor - liquid phase behavior of binary, ternary and multicomponent mixtures of CO2 with other gases. Extensive comparisons with experimental data available in the literature have been performed to validate the predictive and the correlative capabilities of each fluid equation of state. Calculations have been also ii extended to modeling the two and multiphase solid – fluid equilibria of binary CO2 mixtures, so that the effect of impurities on the solidification phenomena could be assessed. A new algorithm for the calculation of the solid – liquid – gas (SLG) equilibrium has been developed and different solid modeling approaches have been coupled with various fluid EoS. The resulting models have been validated against experimental SLG data available in the literature.